Operator and operation characteristics: a comparison of low-sales, medium-sales, and large family farm operations in the United States - Johnson, Kamina, author; Seitzinger, Ann, author; Thilmany, Dawn, author; Pendell, Dustin, author; Pritchett, James, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2011)
The paper analyzes operator and operation characteristics for the smaller and mid-sized farms such as regional influences, age, and educational backgrounds of the operators and their spouses according to their return on assets (ROA). These farms were categorized by size based on gross sales and ranked in quartiles according to the ROA.
December 2011.
Keywords: gross sales; assets; costs; operator; operations; farming; mid-sized farms; United States; small farms